2015
DOI: 10.18632/oncotarget.6406
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial retrograde signaling inhibits the survival during prolong S/G2 arrest inSaccharomyces cerevisiae

Abstract: Cell senescence is dependent on the arrest in cell cycle. Here we studied the role of mitochondrial retrograde response signaling in yeast cell survival under a prolonged arrest. We have found that, unlike G1, long-term arrest in mitosis or S phase results in a loss of colony-forming abilities. Consistent with previous observations, loss of mitochondrial DNA significantly increased the survival of arrested cells. We found that this was because the loss increases the duration of G1 phase. Unexpectedly, retrogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Together, these results demonstrate that ρ 0 cells exhibit slow growth characterized by a delayed G1-to-S transition, and thus confirm previous observations of an impaired G1 exit upon mtDNA loss that has been termed the mtDNA inheritance checkpoint (Crider et al, 2012; Veatch et al, 2009; Zyrina et al, 2015). However, the factors mediating the mtDNA inheritance checkpoint, as well as the initial signal that triggers the cell cycle defect, have not been uncovered.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Together, these results demonstrate that ρ 0 cells exhibit slow growth characterized by a delayed G1-to-S transition, and thus confirm previous observations of an impaired G1 exit upon mtDNA loss that has been termed the mtDNA inheritance checkpoint (Crider et al, 2012; Veatch et al, 2009; Zyrina et al, 2015). However, the factors mediating the mtDNA inheritance checkpoint, as well as the initial signal that triggers the cell cycle defect, have not been uncovered.…”
Section: Resultssupporting
confidence: 89%
“…In addition to preventing cellular respiration and decreasing ΔΨm, mtDNA loss promotes nuclear DNA instability and defective cell cycle progression that manifests as an accumulation of cells in G1 phase (Veatch et al, 2009;Zyrina et al, 2015). In an elegant study, Veatch et al showed these two effects to be separate from each other: while the nuclear DNA instability in mtDNA-depleted cells was driven by defective Fe-S cluster protein assembly, the mechanism(s) underlying the cell cycle defect were not uncovered but were found to be independent of Fe-S metabolism (Veatch et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such growth is associated with prolonged cell cycle delay in G2-phase 89. We have also shown that signaling mediated by Rtg-proteins contributes to the severity of S-phase arrest induced by telomere dysfunction 90. At the same time, early studies showed that cell cycle arrest does not prevent mtDNA overreplication 1819.…”
Section: Retrograde Signaling and Cell Cyclementioning
confidence: 91%
“…This is surprising, because for their energy needs cancer cells tend to rely on glycolysis instead of oxidative phosphorylation. Our study with model eukaryotic cells – baker's yeast – provides an explanation: we found that the loss of mtDNA activates a signaling cascade that tightens the S-phase arrest of the cells caused by inactivation of telomerase [ 6 ]. Importantly, this effect was not due to alterations in ATP supply.…”
mentioning
confidence: 99%